Analysis of the CD200R family - Akkaya, M (2011)
Paired receptor families, consisting of multiple genetically and structurally similar but functionally opposite activating and inhibitory cell surface receptors, are among the fine tuners of the immune regulation. Recent studies on the evolutionary origin of these receptor families have suggested links to pathogen driven diversification, according to which activating receptors continuously evolve in order to counterbalance pathogens that try to subvert the immune response by stimulating the inhibitory receptor through their virulence factors. This thesis is about the CD200R paired receptor family. This family consists of an inhibitory receptor CD200R which is expressed on various leukocytes and delivers inhibitory signals upon engagement with its ligand CD200. In this study, the possibility that the activating members of the family evolved under pathogen pressure was investigated. Genomic DNA from twenty two different mice strains was screened for the presence of members of CD200R family. The number of activating receptors varied, CD200RLe and CD200RLc were found to be mutually exclusive and three strains possessed previously unknown members of CD200R family. In addition, the possibility that CD200R family members and other paired receptors interacted directly with bacteria was tested with a new assay but only the interaction of PIR-A1 with <em)s. aureus<="" em=""> was found as previously reported.</em)s.> The rabbit CD200R family has been characterized and ligand receptor interaction between rabbit CD200 and rabbit CD200R has been demonstrated. However, no interaction between rabbit CD200R and a candidate viral CD200 homologue, the M141R protein of myxoma viruses, could be shown. This finding suggested a CD200R independent role for M141R molecule and possibly other homologues in pox viruses. Finally, two novel antibodies (OX131 and OX132) were characterized together with formerly generated antibodies against mouse CD200R family. The binding specificities and their effects on the CD200-CD200R interaction have been shown. This will help usage of these antibodies in various studies on the functionality and distribution of these receptors.